Jusqu’où va la mer ? Une exploration des marges de l’anthropologie maritime - Alix Levain; Pauline Laval (Revue d'ethnoécologie)
Maritime anthropology federates, since the 1970s, numerous research studies on coastal societies. Emphasizing the singularity of the experience of life at sea, maritime anthropology particularly leaned until now on the comparative ethnography of fishing communities in oceanic environments. Societies living close to estuaries and coastal rivers also feel the influence of the sea under various forms, both direct - as the intimacy with the aquatic environment - and indirect. But the place and role of anthropological research addressing this specific experience in the development of the field of the maritime anthropology remains uncertain.Drawing on the comparison of two field studies -fishing activities in the Amazonian estuary of Oyapock and socio-environmental conflicts on the coast of Finistère (France) - this article shows the multiplicity and the changing forms of presence of the sea in coastal, riparian and rural societies. In the context of rapid and complex anthropogenic change, the margins of the maritime space appear as a heuristic viewpoint to explore the material and immaterial transformations, which affect the connections with marine ecosystems and seascapes.The article raises new questions and avenues as regards to the scope and future directions of maritime anthropology, emphasizing the need for an overtaking of the land-sea dialectic and enhanced reflexivity of the observers. To do so, the authors suggest a systemic and phenomenological approach of the sea and the marine element, which in such a perspective should be addressed as a continuous, dynamic and unstable system extending beyond coastal societies.